2017
DOI: 10.1016/j.ijhydene.2017.06.241
|View full text |Cite
|
Sign up to set email alerts
|

Development of the hybrid sulfur cycle for use with concentrated solar heat. I. Conceptual design

Abstract: Development of the hybrid sulfur cycle for use with concentrated solar heat input Highlights  Design options evaluated for hybrid sulfur cycle water-splitting using solar heat  Indirect solar heating with thermal energy storage using falling particle receiver  Continuous operation with liquid-fed electrolyzer, bayonet acid decomposer  Detailed flowsheet with material and energy balances prepared and presented  35.0% LHV cycle efficiency, 17.0% solar-to-H 2 conversion ratio estimated *Highlights (for revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 31 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, phosphoric acid-doped PBI membranes have demonstrated great thermal and chemical stability up to temperatures of 200 • C [17]. Therefore, PBI-based membranes will be tested in this application at temperatures higher than 100 • C, as these high temperatures will lead to higher overall efficiencies in the hybrid sulfur cycle [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, phosphoric acid-doped PBI membranes have demonstrated great thermal and chemical stability up to temperatures of 200 • C [17]. Therefore, PBI-based membranes will be tested in this application at temperatures higher than 100 • C, as these high temperatures will lead to higher overall efficiencies in the hybrid sulfur cycle [18].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the electric input was about 20% of the thermochemical stage input. The overall efficiency of the thermochemical cycle has been reported to be in the range of 30-40% based on the hydrogen LHV [156,157]. Bilgen [158] formulated the thermal efficiency process as follows:…”
Section: Sulfur Ammonia Cyclementioning
confidence: 99%
“…In addition to water as the sole consumed reactant, one or more materials actively participate in the process without being “net” consumed. Many sequences of reactions have been proposed like volatile metal oxide cycles (e.g., Zn/ZnO cycle or SnO 2 /SnO cycle), phase change stoichiometric oxides (e.g., Fe 3 O 4 /FeO cycle , or metal-substituted ferrites cycles ) or multistep cycles (e.g., hybrid sulfur cycle or manganese oxide-based cycle ). However, currently two-step redox active off-stoichiometric metal oxide (MO x ) thermochemical cycles garner most of the ongoing research efforts among the thermochemical water-splitting cycles, either with cerium-based oxides or perovskites. The metal oxide cycles involve only two reactions (one per each step) based on a redox swing between an oxidized and reduced form of a candidate material, MO x , for which the metal ion (M) can assume multiple oxidation states and the oxygen stoichiometry can vary continuously …”
Section: General Operating Principles Of Photoelectrochemical and Sol...mentioning
confidence: 99%